2007
DOI: 10.4310/cag.2007.v15.n1.a4
|View full text |Cite
|
Sign up to set email alerts
|

Non-negatively curved Kähler manifolds with average quadratic curvature decay

Abstract: 491-530.], we prove that the universal cover M of M is biholomorphic to C n provided either that (M, g) has average quadratic curvature decay, or M supports an eternal solution to the Kähler-Ricci flow with non-negative and uniformly bounded holomorphic bisectional curvature. We also classify certain local limits arising from the Kähler-Ricci flow in the absence of uniform estimates on the injectivity radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…Then by the monotonicity of the eigenvalues of the Ricci curvature in t [13] (Theorem 6.1), the Ricci curvature at p is uniformly bounded below away from zero for all t. On the other hand, by the LYH type differential inequality by Cao [6], we know that d dt R(p, t) ≥ 0. Hence as in [12], for any t i → ∞, (M, g(t i ), p) will subconverge to a gradient Kähler-Ricci soliton with positive Ricci curvature and nonnegative holomorphic bisectional curvature. Hence as in the proof of Theorem 2.4, we can prove that there exist T > 0 and some a > 0 such that for t ≥ T there exists q(t) ∈ B t (p, a) which is the unique point satisfying ∇ t R(q(t), t) = 0 in B t (p, 3a).…”
Section: Proof First Consider the Case That G(t)mentioning
confidence: 96%
See 4 more Smart Citations
“…Then by the monotonicity of the eigenvalues of the Ricci curvature in t [13] (Theorem 6.1), the Ricci curvature at p is uniformly bounded below away from zero for all t. On the other hand, by the LYH type differential inequality by Cao [6], we know that d dt R(p, t) ≥ 0. Hence as in [12], for any t i → ∞, (M, g(t i ), p) will subconverge to a gradient Kähler-Ricci soliton with positive Ricci curvature and nonnegative holomorphic bisectional curvature. Hence as in the proof of Theorem 2.4, we can prove that there exist T > 0 and some a > 0 such that for t ≥ T there exists q(t) ∈ B t (p, a) which is the unique point satisfying ∇ t R(q(t), t) = 0 in B t (p, 3a).…”
Section: Proof First Consider the Case That G(t)mentioning
confidence: 96%
“…By passing to a subsequence still denoted by t i , we can find 0). Thus Z i = f i is a holomorphic vector field, and it can be shown that the gradient of f is zero at the origin (see [12] for example), which is an isolated zero because f ij = R h ij > 0. In fact by its construction in [12, §2] and [6], there exists 0 < r 1 < r such that Z is the unique solution of the equation…”
Section: ) With Positive Ricci Curvature and Bounded Nonnegative Holmentioning
confidence: 99%
See 3 more Smart Citations